EVALUATION OF ENERGY CONSERVATION POLICY IMPLEMENTATION AS ONE OF THE EFFORTS TO REDUCE GLOBAL WARMING - dkk, Sundari (BPPT)
Energy conservation is the responsibility of national governments, provincialgovernments, district / city governments, employers and society. In this regard, it is conducted in this study is to examine the extent to which local governments implement energy conservation policies applied in office buildings or government owned office buildings. The study results show that there are 3 (three) categories of the efforts made by the agency that became the target sample. The third category is the category minor, moderate and major. Policies, programs and energy saving measures carried out by UGM and PT. PAL is the major categories (innovative). While the energy saving measures undertaken by the agency PUP - ESDM provinces DIY is in the middle category. The results of the energy savings made by the agency that became the target sample benefits budget savings in the payment of electricity bills. Cost Benefit Analysis of results showed that the replacement of some facilities building electric-poweredoffice equipment with energy-efficient appliances provide financial benefits in the form of significant budget savings. The role of leadership commitment will determine the successful implementation of energy saving programs and water. Fossil energy savings will decrease the GHG emissions .keywords : global warming, cost benefit, energy conservation